2021
DOI: 10.2991/ahsr.k.210115.095
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Family Support on Self Efficacy of Chronic Kidney Disease

Abstract: Introduction: Patients with chronic kidney disease must be able to undergo hemodialysis therapy, medication, fluid restriction, and diet. Self-efficacy of patients is needed so that all therapies can work well. Besides, family support is no less important so that patients are confident and able to undergo self-management. Method: This research is a quantitative study using, a cross-sectional approach. The research sample was 48 respondents. The research instrument used a family support questionnaire and self-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(16 reference statements)
1
3
0
1
Order By: Relevance
“…According to the results, there was a positive and significant correlation between the domains of the chronic kidney disease self-efficacy questionnaire (independence, organization, problem-solving, and seeking social support) with all domains of the patient's family resilience questionnaire (belief system, organizational model and process). Isnaini et al (2021) studied hemodialysis patients and found a strong relationship between family support and patient self-efficacy so patients with chronic kidney disease need family support [35]. Yin et al (2022) investigated chronic cancer patients and reported that the self-efficacy of these patients has a significant relationship with the resilience of the patients' families (p < 0.001), which was in line with the present study [56].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…According to the results, there was a positive and significant correlation between the domains of the chronic kidney disease self-efficacy questionnaire (independence, organization, problem-solving, and seeking social support) with all domains of the patient's family resilience questionnaire (belief system, organizational model and process). Isnaini et al (2021) studied hemodialysis patients and found a strong relationship between family support and patient self-efficacy so patients with chronic kidney disease need family support [35]. Yin et al (2022) investigated chronic cancer patients and reported that the self-efficacy of these patients has a significant relationship with the resilience of the patients' families (p < 0.001), which was in line with the present study [56].…”
Section: Discussionsupporting
confidence: 88%
“…High levels of social support promote psychological resilience and positive psychological outcomes for maintaining a person's physical and mental health [34]. Recent studies show that social support, including support from spouses, family members, and friends, is significantly related to the health of chronic patients [32] Family support is very important, so that patients have self-confidence and can be under self-management, which may lead to more selfefficacy [35]. In our country, the social support is done mainly by patient's family and other significant persons who have an intimate relationship with patients.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, specific self-efficacy and health literacy scales have been developed for some chronic diseases such as diabetes mellitus. In the literature, the results of studies with self-efficacy assessment tools 38 developed specifically for CRF patients are available. 39,40 However, although there is no measurement tool assessing CRF-specific health literacy, it is seen thar that studies have used general health literacy assessment tools, and that the health literacy level of CRF patients is generally insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil penelitian ini sejalan dengan penelitian Isnaini et al (2020) yang menunjukkan pvalue 0,000 < 0,05 dimana ada hubungan yang kuat antara dukungan keluarga dengan efikasi diri pasien gagal ginjal kronik yang sedang menjalani terapi hemodialisa. Hasil penelitian Novitasari & Wakhid (2018) mengatakan hal yang sama dimana diperoleh nilai p-value 0,000 < 0,05 bahwa terdapat hubungan dukungan keluarga dengan efikasi diri pasien gagal ginjal kronik yang menjalani hemodialisa.…”
Section: Pembahasanunclassified